Indeterminate cell histiocytosis. - Cerroni, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Indeterminate cell histiocytosis is a rare tumor of dendritic cells, poorly defined from a histogenetic point of view. It is characterized by a proliferation of dendritic cells with the same phenotype of Langerhans cells, namely positive for CD1a and S-100 protein, but not presenting Birbeck granules. The lack of the latter coincides with the negativity of the immunohistochemical staining with Langherin (CD207). Therefore, the negativity of Langherin can replace the ultrastructural finding (1). The disease, which often involves the skin, separately or together with other organs, mainly affects old women. However a dozen cases were reported in children (2), with variable prognosis and treatment, from a conservative approach to chemotherapy.